Intention and behavior towards green consumption among low-income households - Al Mamun, Abdullah; Mohamad, Mohd Rosli; Yaacob, Mohd Rafi; Mohiuddin, Muhammad (Elsevier, 2018)
In order to address the issues of climate change through wise management of resources and environmental conservation, this study examined the intention and behavior towards green consumption among low-income households. This study was a cross-sectional that relied on 380 low-income household respondents who lived in coastal areas of Peninsular Malaysia. The findings revealed a positive effect of eco-literacy and self-efficacy on attitude towards green products. Subsequently, the findings also ascertained a positive effect of attitude and perceived behavioral control on intention and consumption of green products. In addition, both scholars and policymakers can rely on these findings to increase the intention and behavior towards the consumption of green products in order to reduce the environmental vulnerability to the coastal communities. Therefore, responsible organizations should implement programs and policies that minimize the adverse effects of climate change through resource management and environmental conservation by promoting the use of green products among Malaysians.